2017
DOI: 10.1016/j.cub.2017.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Stimulation of the Nucleus Basalis of Meynert Improves Working Memory in Adult Monkeys

Abstract: Summary Acetylcholine in the neocortex is critical for executive function [1–3]. Degeneration of cholinergic neurons in aging and Alzheimer’s Dementia is commonly treated with cholinesterase inhibitors[4–7], however, these are modestly effective and are associated with side-effects, which preclude effective dosing in many patients [8]. Electrical activation of the Nucleus Basalis (NB) of Meynert, the source of neocortical acetylcholine [9,10] provides a potential method of improving cholinergic activation [11,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 59 publications
6
60
1
Order By: Relevance
“…In present study, we demonstrated that donepezil pretreatment could improve the performance of working memory in adult mice after anesthesia and surgery, which showed similar results to Ruifeng Liu's findings in adult monkeys (Liu et al, 2017). Donepezil is a medicine approved by the FDA and could improve cognition for the patients with Alzheimer's disease and stroke traumatic brain injury and even for normal older adults (Berthier, Hinojosa, Martin Mdel, & Fernandez, 2003;Black et al, 2007;Yesavage et al, 2002;Zhang, Plotkin, Wang, Sandel, & Lee, 2004).…”
Section: Discussionsupporting
confidence: 85%
“…In present study, we demonstrated that donepezil pretreatment could improve the performance of working memory in adult mice after anesthesia and surgery, which showed similar results to Ruifeng Liu's findings in adult monkeys (Liu et al, 2017). Donepezil is a medicine approved by the FDA and could improve cognition for the patients with Alzheimer's disease and stroke traumatic brain injury and even for normal older adults (Berthier, Hinojosa, Martin Mdel, & Fernandez, 2003;Black et al, 2007;Yesavage et al, 2002;Zhang, Plotkin, Wang, Sandel, & Lee, 2004).…”
Section: Discussionsupporting
confidence: 85%
“…Our study demonstrated that intermittent NB stimulation improves performance of monkeys in a working memory task that requires selective maintenance of a stimulus in memory, in agreement with recent studies that showed similar effects for other memory and attention tasks Liu et al, 2017Liu et al, , 2018. We additionally show that the effect was associated with changes in the firing rate of neurons in the dorsolateral prefrontal cortex, most often increasing it.…”
Section: Discussionsupporting
confidence: 92%
“…At the end of the trial that exceed the 45 s threshold, stimulation was applied anew and the cycle was repeated. This pattern of stimulation was elected based on recent results demonstrating the intermittent stimulation improves working memory and attention performance Liu et al, 2017Liu et al, , 2018. Behavioral performance in our task generally improved with intermittent stimulation ( Fig.…”
Section: Stimulation Effects On Behavioral Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The stimulation is likely to drive the dense population of cholinergic neurons of the NBM, functionally associated with control of attention and maintenance of arousal, both key functions for learning and memory formation (611). Studies in aged rhesus monkeys show intermittent NBM stimulation to induce supranormal working memory and sustained attention (12,13), suggesting that the current pattern of stimulation used in the clinic may not be optimal (14). Accordingly, in the present study, we aimed at comparing the cognitive benefits elicited by intermittent and continuous NBM stimulation in an animal model for AD (TgF344-AD rat line; TG), i.e.…”
Section: Introductionmentioning
confidence: 99%